Designing of Goods Separation Conveyor using GM65 QR Code Scanner Sensor - Nadia, Izzatul Fitri; Hambali, Hambali (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The sorting or separation process is crucial in the delivery of goods or packages, especially when viewed from the many regions in Indonesia. From the management system of separating goods which is generally still done manually, causing some goods to experience destination errors and delivery delays or commonly called Criss-Cross (CC). Delivery delays are also influenced by human error factors, so special tools are needed to separate goods based on the destination city of the goods, one of which uses a conveyor with a GM65 QR Code Scanner sensor. This sensor works based on commands from Arduino which has been programmed in such a way that it can control all inputs and outputs used in the system. In this system, the goods to be separated are made in the form of 3D mode boxes, where each box is affixed with a different QR code, namely A, B, and C. Each QR code represents the destination city of the goods to be separated, namely city A and city B, but for QR code C indicates data other than city A and city B which will be separated as foreign goods so that in this case it does not match any separation. After testing, the tool can work properly and obtain the results of separating goods in the form of a type of QR code that is read with the destination city of each item that has been separated.